Association between statin use and the risk of colorectal cancer in patients with inflammatory bowel disease: a systematic review and meta-analysis - Ding, Meng; Liu, Yang; Zhang, Ying; Qiu, Yunfeng (Frontiers in Immunology, 2026)
BackgroundPatients with inflammatory bowel disease (IBD) are at increased risk of colorectal cancer (CRC). Statins exhibit anti-inflammatory and anticancer properties, and although prior meta-analyses have suggested a possible reduction in CRC risk among patients with IBD, the evidence remains limited by small study numbers and methodological constraints.MethodsWe conducted a systematic review and meta-analysis of observational studies comparing CRC incidence between statin users and non-users in IBD populations. PubMed, Embase, and Web of Science databases were searched for relevant studies on May 22, 2025. Data were pooled using a random-effects model, and relative risks (RRs) with 95% confidence intervals (CIs) were calculated. Subgroup and meta-regression analyses were performed to explore potential effect modifiers.ResultsNine datasets from seven studies involving 639,595 IBD patients were included. Statin use was associated with a significantly reduced CRC risk (RR = 0.77, 95% CI: 0.69–0.87; I² = 27%). The association remained robust in sensitivity analyses and was stronger in high-quality studies (RR = 0.65, 95% CI: 0.54–0.78; I² = 0%). Meta-regression identified follow-up duration as a significant modifier (p = 0.03), and subgroup analysis confirmed that studies with >5 years of follow-up reported a greater risk reduction (p for subgroup difference = 0.02). No significant publication bias was detected (Egger’s test p = 0.35).ConclusionsStatin use is associated with a lower risk of CRC in patients with IBD, particularly in studies with longer follow-up. These findings support further research on the chemopreventive potential of statins in this high-risk population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251038799.